Review of the shock responsive safety net for human capital project – Somalia - Bliznashka, Lilia; Nwabuikwu, Odiche; Diatta, Ampa Dogui; Ray, Soumyajit; Iruhiriye, Elyse; Gelli, Aulo (CGIAR, 2024)
Somalia is one of the world’s poorest countries, ranking last among 193 countries and territories on the 2023–24 Human Development Index. In 2022, 54% of the Somali population, or 15.5 million people, lived below the poverty line. Somalia suffers from extreme food insecurity: 4 million people live in crises or emergency food insecurity. Malnutrition is highly prevalent, with 15% of women and 23% of children underweight. Child stunting affects 28% of children. Overweight and obesity in women are also high at 22% and 11%, respectively. Social protection programs (SAPs) can serve as platforms to reach women and children at scale —serving not only to enhance access to food but also to improve their nutrition and health outcomes. In 2019, the Federal Government of Somalia launched an inaugural government-led national safety net program, known as Baxnaano. The program comprises nutrition-linked unconditional cash transfers, institutional capacity building, and development of a universal social registry.